Journalism issues in Sheki’s literary environment in the 20th century (based on the creativity of Mustafa bey Alibeyov, Nurpasha Hummetov and Tofig Gaffarov) - Adishirinov, K.F. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The article describes the development of journalism in Shaki in the 20th century. The main goal of the author is to highlight the influence and role of publicity in the development of the literary environment in Sheki. The role of the regional press in the development of journalism and some examples of the journalistic legacy of Mustafa bey Alibeyov, Nurpasha Hummetov and Tofig Gaffarov, who were talented publicists of the time, are systematized by the researcher and taken as the object of analysis. The article stands out for its scientific innovation as an initial step in the study of journalistic heritage in the Sheki literary environment.
ХХ ғасырдағы Шеки әдеби ортасындағы журналистика мәселелері (Мұстафа бей Әлібеков, Нұрпаша Гумметов және Тофик Гаффаров шығармашылығы негізінде)
Проблемы журналистики в литературной среде Шеки в ХХ веке (на основе творчества Мустафы бея Алибекова, Нурпаши Гумметова и Тофика Гаффарова)
Keywords: publicism; publicist; article; “Sheki worker”; “Ipekchi”; N. Hummetov; T. Gaffarov; Mustafa bey Alibeyov